RUMAH SEHAT DAN RAMAH GEMPA DI KABUPATEN SAMOSIR - Damayanti, Dwi Putri; Silitonga, Shanty; Pakpahan, Raimundus (Unika Santo Thomas, 2019)
Samosir Regency does not yet have a habitable residence because of limited income, so many of the people live in the villages. In addition, the Samosir region is also an earthquake prone area. Researchers aim is to create livable houses that are able to meet the health requirements and meets the need of resident in Samosir Regency. The design also requires special research on healthy and earthquake-friendly house. The method that will be used in this design are 6 (six) steps, namely ideas / ideas, information, analysis, synthesis, evaluation, and action. Based on the results of the analysis that has been carried out, the use of red brick with a continuous foundation of river stone is the choice of a good structure for earthquake-friendly homes in Samosir district. This residential modeling also included the social elements of Batak Toba culture into it so that this housing could only be applied in the Samosir Regency area.